Experimental Mathematics. Volume 17, Number 1, 2008 - A K Peters (A K Peters, 2009)
Base-Tangle Decompositions of n-String Tangles with 1 < n < 10 Full TextPDF (638.8 KB) Authors Mitsuyuki Ochiai and Noriko Morimura 1-8 No access to content Constructing Packings in Grassmannian Manifolds via Alternating Projection Full TextPDF (527.8 KB) Authors I. S. Dhillon, Jr. R. W. Heath, T. Strohmer and J. A. Tropp 9-35 No access to content On the Failure of the Gorenstein Property for Hecke Algebras of Prime Weight Full TextPDF (291.9 KB) Authors L. J.P. Kilford and Gabor Wiese 37-52 No access to content The van der Waerden Number W(2, 6) Is 1132 Full TextPDF (702.7 KB) Authors Michal Kouril and Jerome L. Paul 53-61 No access to content On the Folkman Number f(2, 3, 4) Full TextPDF (190.7 KB) Authors Andrzej Dudek and Vojtěch Rödl 63-67 No access to content The 2-adic Valuation of Stirling Numbers Full TextPDF (682.1 KB) Authors Tewodros Amdeberhan, Dante Manna and Victor H. Moll 69-82 No access to content Strong Diophantine Triples Full TextPDF (186.9 KB) Authors Andrej Dujella and Vinko Petričcević 83-89 No access to content On the Convex Closure of the Graph of Modular Inversions Full TextPDF (423.5 KB) Authors Mizan R. Khan, Igor E. Shparlinski and Christian L. Yankov 91-104 No access to content Some Heuristics about Elliptic Curves Full TextPDF (622.5 KB) Author Mark Watkins